2019
DOI: 10.3897/phytokeys.135.39036
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Chrysosplenium (Saxifragaceae) from Northeastern China

Abstract: This study describes and illustrates Chrysosplenium macrospermum Y.I.Kim & Y.D.Kim, a new plant species from Changbaishan Mt. (Baekdusan Mt.) in northeastern China. The species is most similar to Chrysosplenium valdepilosum in the series Pilosa but is readily distinguishable by short arching sterile branches, multiple (up to 3) flowering stems, and smooth surfaced seeds (without tubercles), which are ca. 30–50% larger than those of other members in the series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…During the trip an unknown species of Chrysosplenium was collected. Following a thorough literature survey (Hara 1957;Pan 1992;Pan and Ohba 2001;Liu et al 2016;Kim et al 2019;Fu et al 2020) along with the molecular and cytological evidence, we confirmed that it is a distinct and undescribed species.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…During the trip an unknown species of Chrysosplenium was collected. Following a thorough literature survey (Hara 1957;Pan 1992;Pan and Ohba 2001;Liu et al 2016;Kim et al 2019;Fu et al 2020) along with the molecular and cytological evidence, we confirmed that it is a distinct and undescribed species.…”
Section: Introductionsupporting
confidence: 70%
“…Chrysosplenium L. (1753) is a perennial herbaceous genus in Saxifragaceae and comprises more than 70 species (Kim et al 2019;Fu et al 2020). Chrysosplenium is distributed in Asia, America and Europe (Pan and Ohba 2001;Soltis 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysosplenium L. (Saxifragaceae) is a small perennial herbaceous genus that comprises ca. 70 species (Kim et al 2019). Chrysosplenium is distributed throughout the temperate regions of the Northern Hemisphere, with high species diversity in eastern Asia, America and Europe (Hara 1957;Pan 1986aPan , b, 1992Pan and Ohba 2001;Soltis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the diversification centres of this genus including ca. 37 species, the majority of which are distributed in south-western, northern and central China, particularly the Provinces of Yunnan, Xizang, Sichuan and Shaanxi (Pan and Ohba 2001;Liu et al 2016;Kim et al 2019).…”
Section: Introductionmentioning
confidence: 99%